Intraoperative graft-related complications are a risk factor for recurrence in arthroscopic Latarjet stabilisation - Kordasiewicz, Bartłomiej (Knee Surg Sports Traumatol Arthrosc, 2019)
PURPOSE: The goal of this study was to evaluate clinical and radiological outcomes after arthroscopic Latarjet stabilisation in anterior shoulder instability. METHODS: Ninety-three patients after primary arthroscopic Latarjet stabilisation were reviewed. Satisfaction, subjective shoulder value (SSV), Walch–Duplay and Rowe scores, and range of motion and stability were evaluated on clinical examination. Computed tomography (CT) was used to analyse graft position and fusion. RESULTS: Ninety patients (96.8%) were available for clinical and 85 for CT evaluation. The mean follow-up was 23.7 months (13–50, SD 7.1) and age at surgery was 26.2 years (16–44, SD 5.6). Intraoperative complications were reported in eight patients (8.9%) and recurrence in three (3.3%). Significantly, two out of three patients with recurrence had intraoperative graft complications (p = 0.0107). Forty-one patients (45.6%) reported the feeling of “subjective return to sport anxiety”. External rotation with arm at the side was 59° (10–90°, SD 20) with 15° (0–70°, SD 17) of loss of rotation. These two factors correlated with results the most. Patient satisfaction was evaluated as 92% (40–100, SD 14) and SSV 90% (30–100, SD12). Revision rate after primary surgery was 10%. CT showed graft healing in 81 (95.3%) patients. A graft position between 2 and 5 o’clock was found in 70 (83.4%) patients and flush to the anterior glenoid rim in 34 (40.5%). Osteolysis of the superior part of the graft was found in 55 (64.7%) patients. CT evaluation showed no correlation with clinical results. CONCLUSION: Arthroscopic Latarjet stabilisation demonstrates satisfactory results in short-term follow-up; however, intraoperative graft-related complications are a risk factor for recurrence. “Subjective return to sport anxiety” and loss of external rotation with the arm at the side are factors worsening the results. Graft position imperfections and osteolysis of the superior part of the graft reported in CT evaluation do not influence the clinical results.